Pembelajaran Group Investigasi Meningkatkan Hasil Belajar Siswa - Indrawati, Indrawati (Universitas Negeri Makassar, 2018)
The aims of this research is to increase the students learning achievement in opening retail bussiness through cooperative learning with Group Investigation (GI) type in SMK Negeri 1 Makassar.This research is a qualitative research. It is aclass action research which analyze the data into two cycles consist of planning, action, observation and evaluation. The subject of research is XII Marketing1 class of SMK Negeri 1 Makassar as many as 31 students. The result of the research shous that the students have not very clear with this learning condition in the first cycle. So they were given explanation about the learning steps of Group investigation. In the second cycle, teacher and students could understand the implementation og Group Investigation learning model and show a great result. Considering the result of the cycles, it was concluded that the implementation of cooperative learning Group Investigation type could effective increase the learning achievement of opening retail business for XII Marketing 1 students of SMK Negeri 1 Makassar.